DAFE'-E-SART'AN (ANTICANCER) ACTIVITY OF T'AH'LAB (SPIRULINA) - A REVIEW - MD ANZAR ALAM,; NAFIS HAIDER,; SADIQUE HUSAIN,; SHAMIM AHMAD,; TANWIR ALAM, (International Journal of Pharma and Bio Sciences, 2013)
T'ah'lab (Ø·ØÙ„Ø¨) is an Arabic word which means a green substance float on the surface of water, commonly known as algae/spirulina. Spirulina is a photosynthetic, filamentous, spiral-shaped, multicellular and green-blue micro alga. There are many species of spirulina, mainly two: Spirulina maxima and Spirulina platensis, which are used for medicinal purposes. Spirulina is painstaking as an excellent food, lacking toxicity. Spirulina has carotenoids, chlorophyll and the unique blue pigment phycocyanin. Phycocyanin can provide admirable health benefits have been identified to include immuno-modulator, anti-oxidant, anti-cancer, anti-obesity, hypoglycaemic, anti-hyperlipidemic, anti-inflammatory, anti-hypertensive, anti-asthmatic, anti-microbial, anti-parasitic and neuro-protective effects. It acts as natural remedy for many ailments for centuries in ancient systems of medicine, e.g. Ayurveda, Unani and Chinese Medicines. After the assessment of literature about spirulina and its medicinal value, it is found that it can treat all ailments except “death”. So, it can also be called as Maddat-ul-hayat/Aab-e-hayat (elixir of life).